Best Answer

The question is ambiguous because there is no sign shown before the final 6.

Assume it is +6 since -6 would make factorisation very difficult.

Thus the equation is 6b2 - 13b + 6 = 0

Then 6b2 - 4b - 9b + 6 = 0

or 2b(3b - 2) - 3(3b - 2) = 0

ie (3b - 2)(2b - 3) = 0

then 3b -2 = 0 or 2b - 3 = 0

so 3b =2 or 2b = 3

ie b = 2/3 or b = 3/2

🙏

🤨

😮

Study guides

☆☆

Q: Solve by factoring 6b2-13b 6 equals 0?

Write your answer...

Submit

Still have questions?

Related questions

(3x+4)(3x-4)=0 x=±4/3

By factoring. q2 + 16q = 0 q (q + 16) = 0 Now, either q = 0, or q + 16 = 0. Solve those two equations to get the solution.

Re-arranging, x2 - 14x +49 = 0 Factorising, (x-2)(x-2) = 0, hence x=2.

Solve by factoring.2x2 - 3x + 1 = 0

9x2+6x-8 = 0 (3x+4)(3x-2) = 0 Therefore: x = -4/3 or x = 2/3

2sinx+1 equals 0

For y - 2y - 3y equals 0, y equals 0.

y2+7y=18 y2+7y-18=0 (y+9)(y-2)=0 y=-9 & y=2

n2 = 20 + n so n2 - n - 20 = 0 that is (n - 5)(n + 4) = 0 so that n - 5 = 0 or n + 4 = 0 n = 5 or n = -4

a2 + 2a - 3 = 0(a + 3)(a - 1)a = - 3a = 1Simple factoring where you ask yourself; what two factors of - 3 add up to 2?

3x2 = -9 (divide both sides by 3) x2 = -3 (x would have to be the square root of -3) x = ±√-3 x = ±√3i Since you want to solve by factoring: x2 = -3 add 3 to both sides x2 + 3 = 0 x2 - 3i2 = 0 x2 - (√3i)2 = 0 Factor: (x - √3i)(x + √3i) = 0 x - √3i = 0 or x + √3i = 0 x = √3i or x = -√3i

(x + 3)(x - 5)

x: x2 - 81 = 0

many solutions

"x equals 0" is an equality, not an inequality. The question is, therefore, not consistent.

Solve this problem -x squared -40x- 80 =0

x=2

2x2-12x-54 = 0 Solve by factoring or using the quadratic equation formula or by completing the square: (2x+6)(x-9) = 0 Therefore: x = -3 or x = 9

Suppose x3-4x = 0. To solve, factor: x3-4x = x(x2-4) = x(x+2)(x-2) = 0 Now, a product equals 0 if and only one or more of the factors equals 0, so set each factor to 0 and solve. The roots are 0,-2 and +2.

15 = 8x2 - 14x; whence, 8x2 - 14x - 15 = (2x - 5)(4x + 3) = 0. Therefore, x = 5/2 or -3/4.

10x=x 9x=0 x=0

Divide both sides by 8: m = 0

By factoring: x(1-x) = 0 Therefore: x = 0 or x = 1

x2+3x+2=0 (x+2)(x+1)=0 x=-2 or -1

-y + y equals 0.